Museum robot guides or conventional audio guides? An experimental study. (16th December 2020) - Velentza, Anna-Maria; Heinke, Dietmar; Wyatt, Jeremy
Abstract : In the last years, museums around the world began using museum guide robots as an alternative to audio guides. Thus, it is important to identify how these new museum guides can optimally interact with visitors and whether they are more efficient that conventional audio guides. In this paper, we present the results from an experimental study which compared conventional audio guides with robots with different 'personality'. These results demonstrate that people remember significantly more information when they are guided by a cheerful robot than when their guide is a serious one or a conventional audio system. Importantly, we also introduce the idea of two collaborative tour guide robots. This idea was inspired by cognitive studies showing that people remember more when they receive information from two different human speakers. Interestingly, our participants also liked more our collaborative robots, than any version of a single robot and/or audio system. GRAPHICAL ABSTRACT: UF0001